Mindfulness-Based Stress Reduction in Pre-symptomatic Genetic Frontotemporal Dementia: A Pilot Study - Poos, Jackie M.; van den Berg, Esther; Papma, Janne M.; van der Tholen, Fleur C.; Seelaar, Harro; Donker Kaat, Laura; Kievit, J Anneke; Tibben, Aad; van Swieten, John C.; Jiskoot, Lize C. (Frontiers in Psychiatry, 2022)
Pre-symptomatic frontotemporal dementia (FTD) mutation carriers and first-degree family members that are 50% at-risk for FTD may experience symptoms of anxiety and depression as a result of the ambiguity of when or if symptoms of the disease will manifest. We conducted a pilot study to investigate the use of an online mindfulness-based stress reduction (MBSR) course to reduce symptoms of anxiety and depression in presymptomatic frontotemporal dementia (FTD) mutation carriers and individuals 50% at-risk. Seven known mutation carriers and six individuals 50% at-risk completed a standardized 8-week MBSR course, and filled out pre- and post and two-month follow-up questionnaires. The primary outcome measure was the Hospital Anxiety and Depression Scale (HADS). Measures of psychological distress (SCL-90-R), coping style (UCL), quality of life (SF-36) and mindfulness skills (FFMQ) were administered as secondary outcome. Group effects were analyzed with repeated measures ANOVA or Friedman's test, and the individual reliability change index (RCI) was calculated per participant for each outcome measure. Semi-quantitative data included an evaluation and process measure post-intervention. Significant decline was found on the HADS-A post-intervention and after 2 months (p = 0.01), with 54% and 62% of participants demonstrating a clinically significant RCI, respectively. On the HADS-D, significant decline was found 2 months post-intervention (p = 0.04), which was driven by 23% of participants whom had a clinically significant RCI. Additional changes were found between baseline and post-intervention on the seeking distraction and reassuring thoughts subscales of the UCL, the depression and interpersonal sensitivity subscales of the SCL, the observe subscale of the FFMQ, and on physical role limitations of the SF-36 (all p < 0.05). The process evaluation form indicated that the course was found beneficial by participants, and that they applied it in a wide range of everyday situations. This exploratory pilot study indicates the feasibility of MBSR in reducing anxiety and depression in presymptomatic FTD mutation carriers and 50% at-risk individuals. A randomized controlled trial is necessary to replicate these results.